PROMOTION OF THE EFFICIENCY OF THE ENTRY IN THE PREPARATION OF THE MANAGEMENT BODIES IN VIYSK PARTS OF THE NATIONAL GUARDS OF UKRAINE - Adamchuk, Maksym; Lugovskoy, Igor; Afanasiev, Volodymyr (Honor and Law, 2022)
The article lists the problems that may arise during operational training activities in the military units of the National Guard of Ukraine. Analysis of the existing regulatory and legal support, as well as research has shown that the use of simulation tools during command and staff exercises (training) is not fully paid attention. Although the capabilities of modern computer technology and the existing large number of calculation programs can increase the efficiency and accuracy of decisions. In the article the concept of training of governing bodies means a set of planned and comprehensively prepared activities aimed at achieving coherence in the preparation and implementation of combat (special) tasks of the NG of Ukraine, acquisition or improvement of officers' skills to perform functional duties as part of staff and temporary departments, divisions, offices (groups) and other structural units of government. It is proposed to introduce into the staff of the leadership the assistant chief of staff of the leadership on the use of simulation of combat operations, who is responsible for: organizing the work of the department of simulation of combat operations; database development (script); preparation of hardware and software complex; distribution of the audience and jobs with simulation tools according to the positions held; maintenance and proper operation of simulation tools during training; preparation of parsing materials (using the capabilities of simulation tools). The introduction of means of simulation of combat operations during command and staff exercises (training) has a number of advantages: efficiency and accuracy of operational and tactical calculations required for decision-making; ensuring the safety of students in comparison with the classic formats of training with the use of military equipment and weapons; use of electronic maps that allow you to change the scale of the territory, determine distances; low financial costs for training and education; reduction of document flow and speed of information exchange without leaving the workplace; objective assessment of the actions of learners.